Modelling of Heat Affected Zone in Submerged arc Welding Butt Joint with Thorough Penetration. (2017) - Winczek, Jerzy; Parkitny, Ryszard
Abstract: Three-dimensional temporary field for butt welding with thorough penetration was described on the basis of analytical methods of an integral transformation and Green's function. Computations of temporary temperature field have been conducted for one-side butt welded of two steel flats made from S235 steel. Fusion zone has been determined by melting point. Full and partial transformation zones have been limited by temperature values at the beginning and at the end of austenitic transformation. Metallographic researches of the butt joints, which were arc welded under a flux, were carried out in the empirical part of this work. Their results enabled the verification of the numerical simulation results of the temperature field and determined heat affected zones.